Keabsahan Jual Beli atas Objek Jaminan Hak Tanggungan oleh Bank yang dilakukan Tanpa melalui Mekanisme Lelang - Anjel Ria Meiliva Kanter; Moch Bakri; Imam Koeswahyono (Faculty of Law Hang Tuah University, 2017)
The Sale and Purchase of the mortgage lending object is intended to pay off the loan from the debtor. Based on the background, then as for the formulation of the problem of writing is a. How does the validity of the sale and purchase of the object of guarantee of mortgage rights by the bank conducted without through the auction mechanism? b. What are the legal consequences for the sale and purchase of the mortgage guarantee object by the bank which is conducted without the auction mechanism? The research method used is normative juridical research with approach approaches statute approach, conceptual approach, case approach (Case Approach). The result of this research is the Sale and Purchase of the object of mortgage guarantee which is done under the hand and without the debtor's consent is a unlawful act where the sale and purchase of the mortgage security object is contrary to the provisions set forth in Article 6 and Article 20 of Law no. 4 Year 1996 Concerning the Rights of Consumers therefore the sale and purchase of a guarantee maternity guarantee is null and void or it is deemed that there has never been any sale. Furthermore, the Sale and Purchase of the underwriting object under the hand is contrary to Article 20 paragraph 1 (one), paragraph 2 (two), and paragraph 3 (three) of Law no. 4 of 1996 Concerning the Deposit Rights shall have legal consequences for the Creditor as the seller and PPAT as the Officer making the Sale and Purchase Certificate as well as for the Buyer who has good trade